Strategi Komunikasi Pemasaran Menggunakan Analisis SWOT PT. POS Indonesia Cabang Karawang - Muhamad Paisal Aristama; Citra Savitri; Syifa Pramudita Faddila (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
At this time the shipping service provider business is growing so rapidly in Karawang Regency that it is a threat to business competition. PT POS Indonesia Karawang branch must immediately start establishing an accurate marketing communications strategy mix. In order to be able to compete and not be left behind. This study aims to explain and find out the marketing communication strategy at PT POS Indonesia Karawang branch which is appropriate by using SWOT analysis with descriptive quantitative research methods. The research data were obtained from interviews and observations with the Head of Mail, Package and Logistics Business Sales Division and 1 Spv Service and Marketing division at PT POS Indonesia Karawang branch by asking several question points related to the variables Strengths, Weaknesses, Opportunities, Threats. The results of this study obtained the SWOT matrix with an IFAS value of 0.572 and an EFAS of 0.123, where entering into quadrant I supports aggressive strategies, the strategy that must be carried out is market penetration, market growth, market development through promotion development and service innovation as well as carrying out integrated strategies, marketing communication strategies that are in accordance with company conditions are to support aggressive strategies, PT POS Indonesia Karawang branch must start a marketing communication strategy through print media advertising, sales promotion with discounts & cashback, personal selling carried out by each employee, promotion via internet social media such as Facebook, Instagram or all at once Youtube. Keyywords: Factor & Matrix IFAS-EFAS, Marketing communication strategy, SWOT Analysis